Cooperative Communicative Strategies and Tactics as Means of English Business Discourse Harmonization - A. V. Radyuk (Vestnik MGIMO-Universiteta)
The article investigates the cooperative communicative strategies and tactics of English business discourse. There is a necessity of harmonization of business discourse as a sphere of positional and interest collision. Harmonization is a process of maintaining cooperative communication leading to mutually beneficial results. The pragmatic properties of cooperative communicative strategies enable the speakers not only to achieve the set goal but also to sustain positive relationship with the partner.